Packaging methodologies & processing technique to extend shelf life of local banana (musa paradisiaca corniculata) - Muhammad Luqman Abd Jalil (2013)
Bananas have a very short shelf life and it is very sensitive fruit. If the skin of the banana is damaged, the flesh of the banana also will damage. This research specified in searching the most suitable packaging methodologies and processing techniques, so that banana will last longer than normal. From this research, five type of processing techniques and four type of packaging system was chosen. The processing techniques that were used in these researches are banana chip, dried banana, dried banana coated with honey, dried banana coated with glucose and banana pickle. Type of packaging system that was used in this research is vacuum packaging, plastic sealer packaging, glass jar and plastic container. Indicator that is used for determining the quality and shelf life of the banana is by sensory and quality evaluation. Result showed that there is one process condition that was the most suitable for extending shelf life is dried banana. For the packaging system, the most suitable packaging system that can help to maintain the quality of the banana is vacuum packaging.